Cat-scratch disease presenting as a solitary splenic abscess in an elderly man. (24th March 2015) - Nakamura, Momoko; Kurimoto, Mio; Kato, Takehiro; Kunieda, Takeshige
Abstract : Patients with cat-scratch disease (CSD), which is caused by Bartonella henselae, typically present with local lymphadenopathy with a brief period of fever and general symptoms. Most cases are self-limiting and usually afflict children and young adults. Although rare, CSD can lead to serious complications, especially in immunocompromised patients. These rare complications often require intensive treatment. We describe the case of a 79-year-old man who presented with general malaise and a high fever. The physical examination findings were unremarkable. Of note, the lymph nodes were not enlarged. An abdominal CT scan with intravenous contrast revealed a solitary splenic abscess and no lymphadenopathy. The initial antibiotic treatment was ineffective and a splenectomy was indicated. A history of contact with cats raised the possibility of CSD, which was confirmed by a positive serology test result for B henselae . Antibiotic treatment with azithromycin successfully treated the splenic abscess and splenectomy was avoided.